Manajemen Layanan Mutu Perpustakaan Dalam Meningkatkan Minat Baca Siswa - Rosiana, Rosiana; Hariawan, Rudi; Aryani, Menik (Universitas Pendidikan Mandalika, 2024)
Abstract: This study aims to; (1) describe a quality library collection management system that is relevant to students' learning needs, (2) describe library staff in providing satisfactory services to students, to find out how the principal's role is to increase students' reading interest in school libraries, and (3) to describe library strategies in increasing students' reading interest. This study uses a qualitative approach. The data sources in this study are key informants from the Principal, the Head of the Library, Library Staff, and students. Data collection uses interview, observation, and documentation techniques. Validity testing is carried out by triangulation of techniques and sources. Data analysis is qualitative with the Miles and Huberman interactive model. The results of the study show that: (1) In the management of library collections where the school discusses with subject teachers to find out teaching materials that are relevant to the academic year used and provides a collection of novel books to increase students' interest in reading. (2) The form of library services in providing satisfactory services to students, there are 4 things that library staff do, including the SMAN 1 Kuripan Library making library services an important thing such as helping students in borrowing, searching, returning books according to the needs of students' subjects, maintaining visitor comfort while in the library, providing satisfactory services to students, providing complete facilities and book collections and accuracy in borrowing and returning books. (3) The role of the principal in increasing students' interest in reading in the school library is carried out in several ways such as involving teachers in conducting learning in the library, plans to create a reading corner, plans for 24-hour digital library services and cooperation between the principal and teachers and library staff to realize plans to increase students' interest in reading.Keywords: Management, Library, Reading InterestAbstrak: Penelitian ini bertujuan untuk analisis manajemen perpustakaan dalam meningkatkan minat baca siswa di SMAN 1 Kuripan, dengan fokus (1) sistem pengelolaan koleksi perpustakaan yang berkualitas dan relevan untuk kebutuhan belajar siswa, (2) peran staf perpustakaan untuk memberikan layanan yang bermutu kepada siswa, dan (3) Peran kepala sekolah dalam meningkatkan minat baca siswa di perpustakaan. Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data menggunakan teknik wawancara, observasi, dan dokumentasi. Data analisis secara kualitatif dengan model interaktif Miles dan Huberman. Uji keabsahan dilakukan dengan triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa: (a) pengelolaan koleksi perpustakaan oleh staf yang berkualifikasi akademik yang relevan, serta melibatkan guru mata pelajaran guna memberikan bahan ajaran yang relevan bagi siswa, serta menyediakan koleksi buku novel guna meningkatkan minat baca siswa. (b) peran kepala sekolah untuk pengelolaan layanan perpustakaan yang bermutu kepada siswa dilakukan dengan cara, antara lain; membantu siswa dalam peminjaman, pencarian, pengembalian buku sesuai kebutuhan mata pelajaran siswa, menjaga kenyamanan pengunjung selama di perpustakaan, menyediakan fasilitas dan koleksi buku yang lengkap, dan memberikan informasi tentang ketepatan dalam peminjaman dan pengembalian buku. (3) Peran kepala sekolah dalam meningkatkan minat baca siswa di perpustakaan sekolah dilakukan, yaitu dengan program guru mengadakan pembelajaran di perpustakaan, membuat program pojok baca, membuat program layanan perpustakaan digital 24 jam.Kata Kunci: Manajemen, Perpustakaan, Minat Baca